Facet-engineered TiO2 nanomaterials reveal the role of water–oxide interactions in surface protonic conduction. Issue 1 (13th December 2021) - Kang, Xiaolan; Chatzitakis, Athanasios; Aarholt, Thomas; Sun, Xinwei; Negri, Chiara; Norby, Truls
Abstract : Water adsorption and surface protonic conduction on nanocrystalline TiO2 hydrothermally grown to predominance of different crystal facets. Abstract : Water adsorption and surface protonic conduction have been investigated at 25–400 °C in wet (H2 O and D2 O) atmospheres on nanocrystalline TiO2 hydrothermally grown to a predominance of different crystal facets. In situ Fourier transform infrared spectrometry shows that a portion of the water molecules in the first chemisorbed layer adsorbs dissociatively on the {001} and {100} surfaces, but molecularly on the {101} surface. The next layer of physisorbed molecular water is solid (ice)-like on the {001} and {100} surfaces, a fact that is attributed to relatively strong bonds to the surface terminating hydroxyls. On the other hand, it is looser, liquid-like on the {101} surface due to the lack of rigid hydroxyl groups to bond to. As relative humidity (RH) increases with decreasing temperature, additional water layers physisorb and eventually become liquid-like also on the {001} and {100} surfaces. The differences can be attributed to the different atomic arrangements and surface energies of the different crystal facets. Surface protonic conduction on {001} and {100} dominated samples exhibits high pre-exponentials, indicating a high concentration of sites for dissociative chemisorption, and high activation energies reflecting difficult proton migration in the rigid water layers on those surfaces. The surface protonic conduction on the {101} dominated sample reflects a lower coverage of dissociable water and lower activation enthalpies for protonic migration in the more loosely bonded water. This suggests that, more generally, surfaces with dissociative chemisorption may exhibit high surface protonic conductivity at the highest and lowest temperatures (corresponding to lowest and highest RH, respectively), while surfaces with molecular chemisorption may exhibit a relatively high conductivity (less deep minimum) at intermediate temperatures. H/D isotope effects show that the protonic conduction mechanism changes from Grotthuss to vehicle as the physisorbed water layers gain thickness and become liquid-like. The protonic conductivity decreased when the surface was terminated by more strongly bonded fluoride ions, believed to reflect that they block the sites for water adsorption.